YOUTH EMPLOYMENT IN ZARAFSHAN OASIS: HISTORICAL EXPERIENCE OF NAVOI REGION (British Journal of Global Ecology and Sustainable Development, 2022)
The article examines the historical experience of the Navoi region in the field of youth employment. The importance of laws and regulations of state and local authorities in the formation of employment of young people. Mechanisms for the implementation of state and local youth employment programs at the beginning of Uzbekistan's Independence. The problems of youth employment in the beginning of independence, as well as the actions of local authorities in recent years, have been identified. The ways of solving some problems regarding youth employment in the Zarafshan oasis are considered.